2007
DOI: 10.1507/endocrj.k06-198
|View full text |Cite
|
Sign up to set email alerts
|

Preferable Effect of Pravastatin Compared to Atorvastatin on Beta Cell Function in Japanese Early-state Type 2 Diabetes with Hypercholesterolemia

Abstract: Abstract. While a large numbers of clinical trials using various kinds of statins has been reported, a possible preventive effect on new onset of type 2 diabetes mellitus was shown only by the subanalysis of The West of Scotland Coronary Prevention Study (WOSCOPS) using pravastatin. The aim of this study was to investigate whether pravastatin has a preferable effect on glucose tolerance among statins. An open-label prospective cross-over trial was performed to compare the effect of pravastatin (10 mg/day) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…However, the effect of statins on insulin secretion has been controversial. [43][44][45] A previous study shows that pravastatin does not affect insulin secretion in a pancreatic b-cell line, 45 which is consistent with our result. In contrast, atorvastatin and simvastatin are reported to inhibit glucose-dependent insulin secretion by blocking calcium signaling in b-cells, 43,45 which differs from our result with atorvastatin.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effect of statins on insulin secretion has been controversial. [43][44][45] A previous study shows that pravastatin does not affect insulin secretion in a pancreatic b-cell line, 45 which is consistent with our result. In contrast, atorvastatin and simvastatin are reported to inhibit glucose-dependent insulin secretion by blocking calcium signaling in b-cells, 43,45 which differs from our result with atorvastatin.…”
Section: Discussionsupporting
confidence: 92%
“…4 Pravastatin (PRA), a 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitor (statin), also prevents new onset of DM 5 and improves glucose tolerance in patients. [6][7][8] We and others have shown that PRA upregulates adiponectin messenger RNA expression in adipose tissue 8 and in cultured adipocytes, 9 and prevents the development of DM in animal models. [9][10][11] Clinical studies have also shown that PRA treatment increases plasma adiponectin in patients with hypercholesterolemia and is associated with improved glucose metabolism.…”
Section: Introductionmentioning
confidence: 96%
“…12,13 However, the effect of the combined therapy on glucose intolerance, which often coexists with other risks and worsens prognosis by increasing cardiovascular oxidative stress, remains to be investigated. 5,6,7,, an essential cofactor for endothelial nitric oxide synthetase (eNOS), tends to be oxidized to 7,8-dihydrobiopterin (BH2) in DM. 14 Decreased BH4 limits eNOS dimerization, resulting in decreased nitric oxide (NO) synthesis and increased superoxide production, so-called eNOS uncoupling, and is a major mechanism of endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, atorvastatin has been reported to worsen glycemic control in a few case reports and some clinical trials in Japan. In recent studies that compared pravastatin with atorvastatin directly, the former acted favorably on glycemic control among diabetic 6,7) and non-diabetic patients 8) . These results indicate that the beneficial effect of pravastatin on glucose metabolism is unique among the currently used statins.…”
Section: Introductionmentioning
confidence: 99%